1987
DOI: 10.1042/bj2440087
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action of GTP on Ca2+ efflux from rat liver microsomal vesicles

Abstract: 1. Guanosine 5'-[gamma-thio]triphosphate (GTP[S]), if added before GTP, blocks both Ca2+ efflux promoted by GTP and the effect of GTP on enhancement of inositol 1,4,5-triphosphate (IP3)-promoted Ca2+ release from preloaded microsomal vesicles. If, however, GTP[S] is added after GTP, it does not reverse the Ca2+ efflux promoted by GTP, nor does it inhibit IP3-promoted Ca2+ release. 2. The effect of GTP in enhancing IP3-promoted Ca2+ release is maintained after washing the microsomal vesicles free of added GTP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
38
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 22 publications
7
38
1
Order By: Relevance
“…It was recently suggested that guanosine triphosphate (GTP) could activate Ca2+ release from endoplasmic reticulum in non-muscle cells (Chueh & Gill, 1986;Dawson et al, 1987). In skinned vascular smooth muscle Saida & van Breemen (1987) reported that GTP enhances the InsP3-induced Ca2 + release from sarcoplasmic reticulum, and they suggested that guanine nucleotide-binding proteins are involved in the mechanism of Ca2+ -release.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently suggested that guanosine triphosphate (GTP) could activate Ca2+ release from endoplasmic reticulum in non-muscle cells (Chueh & Gill, 1986;Dawson et al, 1987). In skinned vascular smooth muscle Saida & van Breemen (1987) reported that GTP enhances the InsP3-induced Ca2 + release from sarcoplasmic reticulum, and they suggested that guanine nucleotide-binding proteins are involved in the mechanism of Ca2+ -release.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of rat liver microsomes and the measurements of Ca2+ uptake and release using a Ca2+-sensitive electrode were as described by Dawson et al (1987). Aluminium was solubilized by mixing AICl3 (10 mM) and sodium citrate (50 mM) for at least 2 h prior to use.…”
mentioning
confidence: 99%
“…Therefore we decided to look at possible effects of aluminium on (i) calcium movements in isolated rat liver microsomes, and (ii) Ins(1,4,5)P3 metabolism by the 5-phosphatase and 3-kinase. It should be emphasized that in view of the uncertainties surrounding the kinetics of Al3+ exchange between various chelators (Miller et al, 1989), the media used in our experiments were pre-equilibrated for several hours in plastic containers.The preparation of rat liver microsomes and the measurements of Ca2+ uptake and release using a Ca2+-sensitive electrode were as described by Dawson et al (1987). Aluminium was solubilized by mixing AICl3 (10 mM) and sodium citrate (50 mM) for at least 2 h prior to use.…”
mentioning
confidence: 99%